Effects of Remap-TPS Using Wizer.Me Website and Mindmap Application on Students’ Cognitive Learning Results - Muhammad Ilham A’raafi; Siti Zubaidah; Munzil Munzil; Azizul Ghofur Candra Wicaksono (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
This study aims to determine the Remap-TPS learning model assisted by the Wizer.me website and the MindMup application on students’ cognitive learning outcomes. This quasi-experimental study used a non-equivalent pretest-posttest control group design. The population of this research is was all students of class XI SMA Negeri 8 Malang. The research sample was class XI MIPA 3 as the experimental class and class MIPA 4 as the control class. Cognitive learning outcomes data were obtained from the results of multiple-choice tests and essays. Data were analyzed using the one-way Anacova test. Based on the results of the study, it was shown that Remap-TPS learning assisted by the Wizer.me website and the MindMup application affected students’ cognitive learning outcomes.